Pelayanan Perizinan Berbasis Online Melalui Surabaya Single Window (SSW) Alfa Di Unit Pelayanan Terpadu Satu Atap (UPTSA) Kota Surabaya - Artanti, Dian Febri; Fanida, Eva Hany (Publika, 2024)
Efforts to modernize public service activities have become a goal for the government to reduce the phenomenon of bureaucratic pathology. Such as through the use of technology in the form of electronic government. The e-government that the Surabaya City Government is pursuing, namely licensing services, is presented in the form of the SSW Alfa website. The aim of this research is to describe and analyze the implementation of online based licensing services through SSW Alfa in the one stop integrated service unit (UPTSA) in Surabaya City. The method used is a qualitative descriptive method. The focus of this research uses the theory of electronic government success factors according to (Hafid, 2017). The research method used is descriptive with a qualitative approach. This research was conducted at UPTSA Surabaya City using observation, interview and documentation techniques. This research uses narrative analysis techniques including data collection, data reduction, data presentation and drawing conclusion. The research results show that the application of SSW Alfa operates well, making it easier for applicants to apply for permits. However there are still several problems that need to be fixed, such as an error on the website server so that the proposed service experiences delays in processing files, as well as the use of double website servers to accomodate files that cannot be uploaded via SSW Alfa. Based on the research results, the suggestions given are 1) Surabaya City Diskominfo needs to improve the system so that it is able to accommodate all files via SSW Alfa, 2) Surabaya City DPMPTSP needs to integrate permit services so as not to use multiple systems, 3) Technical Regional Apparatus needs to make adjustments so that processing is systemized through SSW Alfa.